Geomorphology of the Copahue Volcano region and vicinities (Central-western Neuquén) - González Díaz, E.F. (2005)
This thematic map describes the principal features of the landscape, a relative sequence of its geomorphic evolution, and arrives to important conclusions about its regional stratigrapby. The regional landscape is composed and polycyclic. The geoforms are related to different exogenous processes (glacial, fluvial and mass-wasting). An endogenous process (volcanism) formed the more distinctive features; a great tectonic-volcanic caldera and the preglacial Copahue stratovolcano. Some minor and youngest volcanic forms were formed during postglacial times. A previous fluvial cycle was replaced by glacial morphogenesis (valley glaciation) during the Quaternary, due a climatic intervention. A huge and very thick (500-800 m) ice-blister was lodged into the caldera. The ice-blister exceded the caldera's edges forming several glacial diffluences and giving an important and additional supply to neighbouring glacial valleys (Hualcupén and Trocoman), out of to the depression. The Pleistocene glaciation shows two local cycles of volcanic eruptions: pre- and post-glacial. The origin of many local lakes was related to glacial exharation. Others lakes have different genesis: by blocking slide, crater-lake and glacial exharation associated with important structural weakness (Caviahue Lake related to the Trapa-Trapa lineament or Caviahue graben). During postglacial times important rock-avalanches occurred in the Hualcupén valley: the Cajón Chico and Compul rock-avalanches were related to seismic shocks. Previously, their accumulations were interpreted as terminal moraines of a second glaciation. A fluvial rejuvenation phase was the consequence of a blocking of Agrio River by the Agrio volcanic flows, during the Holocene. After that, the river eroded this obstacle restablishing its previous base level. The Agrio cascade represents the upstream present position of the consequent rejuvenation wave. © 2005 Asociación Geológica Argentina.